Morphological and Developmental Traits of the Binucleation of Male Accessory Gland Cells in the Benthic Water Bug, Aphelocheirus vittatus (Hemiptera: Aphelochiridae). Issue 4 (18th August 2020) - Takeda, Koji; Yamauchi, Jun; Adachi-Yamada, Takashi
Abstract: The male accessory glands (MAGs) in insects are pair(s) of internal reproductive organs that produce and secrete the plasma component of seminal fluid. In various insects, MAG size is important for male reproductive success because the fluid provides physiologically active substances and/or nutrients to females to control sperm as well as female reproductive behaviors. Although the MAG epithelial cells in most insect species are standard mononucleate cells, those in some insect taxa are binucleate due to incomplete cytokinesis (e.g., Drosophila [Fallén] [Diptera: Drosophilidae]) or cell fusion (e.g., Cimex [Linnaeus] [Hemiptera: Cimicidae]). In the case of Drosophila, the apicobasal position of the two nuclei relative to the epithelial plane changes from vertical to horizontal after nutrient intake, which allows the volume of the MAG cavity to expand effectively. On the other hand, in the case of Cimex, the positions of the two nuclei do not change apicobasally in response to feeding, but their position relative to the proximodistal axis varies depending on the tubular/spherical organ morphology. Here, we report that the MAG of the benthic water bug Aphelocheirus vittatus (Matsumura) (Hemiptera: Aphelochiridae) shows binucleation in all epithelial cells. Despite the phylogenetically close relationship between Aphelocheirus and Cimex, the MAG cells in Aphelocheirus showed a Drosophila -like apicobasal change in the position of the two nuclei in response to feeding. Furthermore, the cytological processes during binucleation are more similar to those in Drosophila (incomplete cytokinesis) than to those in Cimex (cell fusion). These results indicate that the physiological role and mechanism of binucleation in MAG cells changed during the evolution of Hemiptera.